Determination of the optimal time for N95 respirator for aerosol infection control. Issue 50 (11th December 2020) - Du, Jian; Zhang, Lijie; Liu, Yuhong; Shu, Wei; Ma, Yan; Gao, Jingtao; Li, Liang
Abstract : Abstract: The transmission of tuberculosis has been declared as an important occupational hazard for health care workers of tuberculosis dispensary. Here, we evaluated the filtration efficiency and respiratory resistance of different respirators along with the increase of wear time. Filter efficiency and breathing resistance were tested to determine the performance of different types of respirators, and the N95 respirator were simulatively worn by volunteers to determine the optimal time for N95 respirator as a tuberculosis control measure. N95 respirator had the highest filtration efficiency (97.4% ± 0.3%), whereas the surgical mask could only prevent 18.4% of aerosol particles to penetrate inside the respirator. In addition, N95 respirator and surgical mask had the highest and lowest exhalation resistance (13.8 ± 0.9 mmH2 O vs. 1.8 ± 0.2 mmH2 O), respectively. When the volunteers wore the N95 respirator for 3 days, the average filtration efficiency was 97.0%. In addition, there were no significant differences in the exhalation resistance of N95 respirator, ranging from 13.8 ± 0.9 mmH2 O of 0 day to 11.6 ± 0.9 mmH2 O of 14 days. Our results demonstrate that only N95 respirator provides promising protective efficiency for health care workers against tuberculosis. In addition, N95 respirator could produce adequate protective efficacy after 3-day wear time.